Pelatihan Dasar-Dasar Kepemimpinan Organisasi - Anggriani, Rini; Cahyadi, Irwan; Khairunnisa; Dasriani, Ni Gusti Ayu; Hijjah, Khasnur; Wardhana, Helna (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
The basics of organizational leadership training aim to equip participants with the knowledge, skills and attitudes necessary to become effective leaders in an organizational context. The activity method uses a lecture approach, interactive discussion sessions, and training according to existing conditions. In this training, participants are taught the basic principles of leadership including effective communication, decision making, and understanding various leadership styles in organizations. Indicators of success are shown by the high enthusiasm of participants in participating in activities which is also marked by increased knowledge and skills of participants regarding the basics of leadership. This training activity has an impact on improving individual and team performance, developing organizational culture and increasing overall organizational competitiveness. With the development of the right skills, leaders can lead an organization toward achieving greater goals and create a work environment that grows positively, productively, innovatively, and collaboratively.